Optimized Harvest Management Strategy Based on Latent Loss and Antioxidant Enzyme Activity - Yujia Wang; Wenfu Wu; Jie Xu; Ming Gao; Zidan Wu; Rui Wang; Houqing Liu (Foods)
Timely harvesting is a crucial aspect of agricultural production, requiring the comprehensive evaluation of multiple factors to optimize yield and quality while minimizing economic losses and resource waste. This study systematically investigates the latent loss and changes in antioxidant enzyme activity in maize and soybean (Glycine max) to refine harvest management strategies. The findings reveal that latent loss is a universal phenomenon across different maize and soybean varieties, with maize exhibiting a dry matter loss of up to 12.1036% and soybean reaching 5.5742%. As the harvest progresses, the 1000-grain weight at standard moisture initially increases post-maturity, stabilizes gradually, and may eventually decline, while antioxidant enzyme activity follows a similar trajectory, demonstrating inter-varietal differences. Based on these findings, this study innovatively relates to latent loss and antioxidant enzyme activity. The optimal harvest period for each grain variety is determined step by step to maximize economic benefits, enhance market competitiveness, and ensure the safety and efficiency of grain production.